Symptomatic Follicular Lymphoma: Complete Remission After Chemoimmunotherapy with Bendamustine–Rituximab - Rajabto, Wulyo; Harahap, Agnes Stephanie; Putra, Handy Nugraha (Acta Medica Indonesiana, 2024)
Follicular lymphoma (FL) is the second most common non-Hodgkin lymphoma in Western countries after diffuse large B-cell lymphoma. Most patients with FL present with asymptomatic disease. Survival rates have been rising over time mainly due to advancing therapeutic strategies A-51-year-old male with a history of well-controlled diabetes mellitus treated with insulin presented to the policlinic of hematology-medical oncology with worsening right inguinal lymphadenopathy for >3 months. He had no complaints of prolonged fever, night sweat, or weight loss. Initial physical examination revealed a healthy male with bulky right inguinal lymphadenopathy. The patient was then referred to a surgeon, and excisional biopsy of the enlarged right inguinal lymph nodes was performed. Therefore, stage II bulky symptomatic low-grade FL was established. We administered chemoimmunotherapy with rituximab and bendamustine every 3 weeks for six cycles. The patient tolerated the treatment well and completed six cycles of chemoimmunotherapy, and the follow-up FDG PET/CT showed complete remission of the disease. The patient achieved complete remission after series of chemoimmunotherapy with Bendamustine–Rituximab. Future assessment is still required for this patient to ensure the remission status of the lymphoma